(untitled) (Al-Mansour Journal, 2022)
There is a great need to transfer information between hosts and networks in fast with reliable and secure way; this is a big challenge with open environment especially Internet and TCP based Networks. There are several extra file transfer protocols behind core FTP protocol, but each of them suffer from either slow, unreliable or unsecure workflow. In this paper, we develop a new file transfer protocol based on UDP as a fast, reliable and secure protocol; and called FRS-FTP (refers to Fast Reliable Secure File Transfer Protocol. The proposed protocol based on three phases, the first phase to enforce the "reliability" issue using cryptographic hash checksum, the second phase to enforce the "security" issue using file encryption/decryption, port protection and authentication, while the third phase to transfer files with "fast" issue under UDP. The proposed protocol is implemented using Visual Basic .Net programming language and System.Net.Sockets embedded dot Net Class.